(untitled) (Entrepreneurship Journal for Finance and Business, 2024)
Drugs are among the most serious problems facing modern societies. Their negative effects are not limited to the individual alone but extend to impact all aspects of social, economic, and environmental life. This phenomenon has grown significantly in recent decades, affecting communities regardless of their level of economic or cultural development. Drug abuse is not restricted to a specific group; it spans different ages and social classes, making it a pressing issue to address in order to maintain social stability. The drug phenomenon arises at a time when the world faces significant challenges in sustainable development, which aims to balance economic growth, social justice, and environmental protection. This is where the danger of drugs lies, as they represent an obstacle to achieving these goals. Addiction leads to a decline in the economic productivity of individuals and societies, increases the burden on the healthcare system, and exacerbates crime and violence, hindering efforts to improve the quality of life and achieve social justice. At the same time, drug trafficking contributes to environmental destruction through the excessive exploitation of land and pollution resulting from illegal drug manufacturing and trade. Therefore, sustainable development cannot be achieved in any society without implementing effective strategies to combat the drug phenomenon and reduce its negative impacts.